2012
DOI: 10.1007/s12663-012-0386-2
|View full text |Cite
|
Sign up to set email alerts
|

Gnathic Desmoplastic Fibroma Mimicking a Dentigerous Cyst: A Case Report

Abstract: Desmoplastic fibroma (DF) is a rare, well-differentiated fibrous tumor, which is slow in growth but has an aggressive potential. In its clinical and radiographic presentation it mimics many unusual pathologies of the jaws. This case report presents a DF in the mandible, which in its clinical presentation and radiographic appearance mimicked a dentigerous cyst highlighting the importance of detailed histopathological examination in the diagnosis of jaw pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
0
1
0
2
Order By: Relevance
“…21 On the other hand, Kali et al reported a gnathic desmoplastic fibroma mimicking a dentigerous cyst. 22 The patient described in the present study had received 3 rounds of chemotherapy before the final, more favorable diagnosis of the tumor was made, and several dental anomalies were found in the panoramic radiograph taken a few years after anticancer treatment. The missing upper right canine (tooth 13) was probably a complication of myxoma excision from the upper right sinus.…”
Section: Discussionmentioning
confidence: 78%
“…21 On the other hand, Kali et al reported a gnathic desmoplastic fibroma mimicking a dentigerous cyst. 22 The patient described in the present study had received 3 rounds of chemotherapy before the final, more favorable diagnosis of the tumor was made, and several dental anomalies were found in the panoramic radiograph taken a few years after anticancer treatment. The missing upper right canine (tooth 13) was probably a complication of myxoma excision from the upper right sinus.…”
Section: Discussionmentioning
confidence: 78%
“…A unilocular or multilocular, well-defined or irregular radiolucency with variable expression of marginal sclerosis are among the presented radiographic features. Therefore, DF often mimics other common as well as unusual pathologies of the jaws, including ameloblastoma, odontogenic myxoma, aneurysmal bone cyst, chondromyxoid fibroma, central hemangioma, and dentigerous cyst [ 6 , 7 ]. Two more unusual patterns that have been described are periapical pathology in relation to an endodontically treated tooth and an interradicular position at presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Por se tratar de uma área bastante evidente e que é responsável por grande parte da projeção do terço médio e lateral da face, optou-se em realizar a enucleação da lesão, no intuito de preservar ao máximo o tecido remanescente do osso e arco zigomático, segue com 30 meses de acompanhamento sem recidivas (Escalera, et al, 2010;Kalia, Kaur & Vashisht, 2015.…”
Section: Discussionunclassified
“…Por se tratar de uma lesão que não apresenta características clínicas e radiográficas específicas, o fibroma desmoplásico muitas vezes poderá fazer diagnóstico diferencial com lesões como o ameloblastoma, mixoma odontogênico, cisto ósseo aneurismático, fibroma condromixóide, hemangioma central e granuloma eosinofílico (Chemli, et al, 2009;Kalia, Kaur & Vashisht, 2015;Faulkner, et al, 1995).…”
Section: Introductionunclassified